Plan pursuit in the context of daily fruit and vegetable consumption: the importance of cue detection and the execution of the planned behaviour for overall behaviour change - Domke, Antonia; Keller, Jan; Knoll, Nina; Sniehotta, Falko F.; Heuse, Silke; Wiedemann, Amelie U. (British journal of health psychology, 2022)
Objectives In action planning interventions, individuals specify and link cues with behavioural responses to implement behaviour change. To date, not much is known about how and how much the detection of the planned cue (entering and identifying the planned situation) and the execution of the planned behaviour (behavioural response exactly as planned) contribute to overall behavioural changes (changes in target behaviour) achieved by individuals. Using data from an intervention on daily fruit and vegetable (FV) action planning, this study aimed to test whether individuals’ cue detection and execution of the planned behaviour are positively related to overall FV intake. Design Secondary data analyses examined diary data of the intervention condition of a randomized controlled trial. Ninety participants (80% female, aged 19-63 years) formed one FV plan and completed a 13-days post-intervention self-report diary assessing daily FV consumption and situational characteristics of each consumed FV serving. Based on these self-reports and participants’ FV plan, day-to-day cue detection and the execution of the planned behaviour were coded. Methods With two-level models, cue detection and the execution of the planned behaviour were examined as between- and within-person predictors of daily FV intake. Results Higher between-person execution of the planned behaviour (+1.68 daily servings), higher-than-usual within-person cue detection (+0.46 daily servings), and higher-than-usual within-person execution of the planned behaviour (+0.29 daily servings) were associated with more overall FV intake. Conclusions Detecting planned cues (within-person) and executing the planned behaviour (between- and within-person) are important for overall FV intake.